Modified in vivo comet assay detects the genotoxic potential of 14‐hydroxycodeinone, an α, β‐unsaturated ketone in oxycodone. (13th May 2015) - Pant, Kamala; Roden, Nicholas; Zhang, Charles; Bruce, Shannon; Wood, Craig; Pendino, Kimberly
Abstract : 14‐Hydroxycodeinone (14‐HC) is an α, β‐unsaturated ketone impurity found in oxycodone drug substance and has a structural alert for genotoxicity. 14‐HC was tested in a combined Modified and Standard Comet Assay to determine if the slight decrease in % Tail DNA noted in a previously conducted Standard Comet Assay with 14‐HC could be magnified to clarify if the response was due to cross‐linking activity. One limitation of the Standard Comet Assay is that DNA cross‐links cannot be reliably detected. However, under certain modified testing conditions, DNA cross‐links and chemical moieties that elicit such cross‐links can be elucidated. One such modification involves the induction of additional breakages of DNA strands by gamma or X‐ray irradiation. To determine if 14‐HC is a DNA crosslinker in vivo, a Modified Comet Assay was conducted using X‐ray irradiation as the modification to visualize crosslinking activity. In this assay, 14‐HC was administered orally to mice up to 320 mg/kg/day. Results showed a statistically significant reduction in percent tail DNA in duodenal cells at 320 mg/kg/day, with a nonstatistically significant but dose‐related reduction in percent tail DNA also observed at the mid dose of 160 mg/kg/day. Similar decreases were not observed in cells from the liver or stomach, and no increases in percent tail DNA were noted for any tissue in the concomitantly conducted Standard Comet Assay. Taken together, 14‐HC was identified as a cross‐linking agent in the duodenum in the Modified Comet Assay. Environ. Mol. Mutagen. 56:777–787, 2015. © 2015 Wiley Periodicals, Inc.